2009
DOI: 10.1089/gtmb.2008.0127
|View full text |Cite
|
Sign up to set email alerts
|

TheBRCA13′-UTR: 5711+421T/T_5711+1286T/T Genotype Is a Possible Breast and Ovarian Cancer Risk Factor

Abstract: These results suggest that the inheritance of specific 3'-UTR polymorphisms may predispose individuals to early-onset or familial breast or ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…Our observation in CRC patients correlates well with the results obtained in a several transformed colon cell lines, further suggesting that altered PIGK expression may be an early event in colon carcinogenesis. In a recent study, 3' UTR polymorphisms in the BRCA1 gene were shown to be associated with reduced gene activity and this alteration was proposed as a possible breast and ovarian cancer risk factor (17). Similar to the CRC patients, we observed altered alleles (C/G or G/G) and corresponding low PIGK protein expression in some HCC patients and cell lines.…”
Section: Discussionsupporting
confidence: 72%
“…Our observation in CRC patients correlates well with the results obtained in a several transformed colon cell lines, further suggesting that altered PIGK expression may be an early event in colon carcinogenesis. In a recent study, 3' UTR polymorphisms in the BRCA1 gene were shown to be associated with reduced gene activity and this alteration was proposed as a possible breast and ovarian cancer risk factor (17). Similar to the CRC patients, we observed altered alleles (C/G or G/G) and corresponding low PIGK protein expression in some HCC patients and cell lines.…”
Section: Discussionsupporting
confidence: 72%
“…The ability of miRNAs to bind to the 3'UTR of mRNA is critical for regulating mRNA levels and protein expression, and this binding can be affected by single-nucleotide polymorphisms. Data from our group and others indicate that BRCA1/2 3'UTR variants may be potential genetic markers of breast cancer risk (Pongsavee et al, 2009;Pelletier et al, 2011). It is possible that the c.*1287C>T (rs12516) SNP in the 3'UTR region of the BRCA1 gene reported here could decrease the affinity of binding or create or eliminate new binding sites for some miRNAs.…”
Section: Discussionmentioning
confidence: 65%
“…However, based on fisher's exact test, although no significant association was determined In the present study in Turkish breast cancer patients, two SNPs were detected in the 3'UTR of BRCA1 and BRCA2 at positions c.*1287C>T (rs12516) (BRCA1) and c.*105A>C (rs15869) (BRCA2). In the literature, these polymorphisms are associated with an increased risk of breast/ovarian cancer among familial and early-onset cancer groups, particularly in patients without mutations in the coding sequences of BRCA1 and BRCA2 (Pongsavee et al, 2009;Nicoloso et al, 2010). One study (Sehl et al, 2009) reported that SNPs within or near several double-stranded break repair DNA repair pathway genes are associated with breast cancer in individuals from a high-risk population.…”
Section: Clinical Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…16,[21][22][23][24][25] The first published studies reported two variants: c.*36C4G, identified while screening 211 breast cancer cases, 22 and c.*372_387del16 while screening 78 breast cancer cases belonging to high-risk breast and ovarian cancer families. 25 Pietschmann et al screened BRCA1/BRCA2 coding sequences and 5ʹ-and 3ʹ-UTRs in 10 Iranian high-risk breast cancer families.…”
Section: Discussionmentioning
confidence: 99%